Assisted Problem Based Learning Mobile Learning Application to Improve Preservice Counselor Problem Solving Skills - Kholili, Ma'rifatin Indah; Purwaningrum, Ribut (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
In today's digital era, the need for effective problem solving skills is increasingly urgent, especially for preservice counselors who will play an important role in helping individuals overcome various challenges. This research aims to test the effectiveness of Application-assisted Problem Based Learning (PBL). Mobile Learning (MLA) through the Bikonesia platform in improving the problem solving abilities of guidance and counseling students (school counselors initial service). This research method is descriptive qualitative by using a quasi-designpre-test post-test experiment control group design which was carried out for 8 weeks. The subject of this research is students majoring in guidance and counseling in one academic year Treatment using the PBL process is divided into five stages: Problem analysis and learning, Discovery and reporting, Solution presentation and reflection, Overview, integration, and evaluation. Data was collected using the Problem Solving Skills Scale developed by researchers. Data were analyzed using an independent t test to compare data stop you And post-test. Hypothesis test results show that Sig. This shows that the model Problem Based Learning (PBL) assisted by Application Mobile Learning (Bikonesia) has a significant effect on improving problem solving abilities Preservice Counselor. Future researchers should consider or even test multiple skills simultaneously through PBL. The implications of this research are can encourage educational institutions to integrate mobile technology in the learning process, considering its effectiveness in improving problem-solving skills.